2014
DOI: 10.1371/journal.pgen.1004698
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Expansion of the Hox Cluster in Lepidoptera Generated Four Homeobox Genes Implicated in Extra-Embryonic Tissue Formation

Abstract: Gene duplications within the conserved Hox cluster are rare in animal evolution, but in Lepidoptera an array of divergent Hox-related genes (Shx genes) has been reported between pb and zen. Here, we use genome sequencing of five lepidopteran species (Polygonia c-album, Pararge aegeria, Callimorpha dominula, Cameraria ohridella, Hepialus sylvina) plus a caddisfly outgroup (Glyphotaelius pellucidus) to trace the evolution of the lepidopteran Shx genes. We demonstrate that Shx genes originated by tandem duplicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 56 publications
7
71
0
Order By: Relevance
“…Our results raise the possibility that gene and genome duplications could be associated with major transitions in insect evolution. The route to such profound transitions might involve the introduction of novelty via duplication, as has been shown in the expanding Hox genes of some Lepidoptera (Ferguson et al 2014) . Our results lend support to long-standing hypotheses that gene and genome duplications are important forces in animal evolution (Ohno and Susumu 1970;Van de Peer et al 2009) .…”
Section: Discussionmentioning
confidence: 99%
“…Our results raise the possibility that gene and genome duplications could be associated with major transitions in insect evolution. The route to such profound transitions might involve the introduction of novelty via duplication, as has been shown in the expanding Hox genes of some Lepidoptera (Ferguson et al 2014) . Our results lend support to long-standing hypotheses that gene and genome duplications are important forces in animal evolution (Ohno and Susumu 1970;Van de Peer et al 2009) .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the origin of Shx genes, we determined low-coverage genome sequences for five additional lepidopteran species chosen for phylogenetic position, plus a caddisfly outgroup [52,54]. Assembly and analysis revealed that the Bombyx situation is unusual, whereas possession of four distinct Shx genes (ShxA, ShxB, ShxC, ShxD) is typical for a large clade within Lepidoptera, encompassing butterflies (Heliconius, Polygonium, Pararge), tiger moth (Callimorpha) and Gracillariidae (Cameraria).…”
Section: Extra Hox Genes and The Evolutionary Success Of Lepidopteramentioning
confidence: 99%
“…The basal Orange swift moth also has zen duplicates, but without extensive divergence. (b) Localized ShxC RNA marks the presumptive serosa in developing oocytes of the speckled wood butterfly Pararge aegeria [52]. All four Shx genes are expressed in serosa as it develops.…”
Section: Glyphotaelius Pellucidus Caddisfly 4x 4xmentioning
confidence: 99%
“…However, many bilateral animals have a disorganized HOX cluster with no obvious impact on their body plan (Duboule ). Hox gene number and order is highly flexible within some genera (e.g., Drosophila ) and phyla (e.g., Nematoda, Mollusca, Urochordata, Arthropoda) (Aboobaker and Blaxter ; Seo et al ; Negre and Ruiz ; Ferguson et al ). Therefore, Hox genes do not need to be organized in an intact cluster for proper development of the A‐P axis (Monteiro and Ferrier ; Negre and Ruiz ).…”
Section: Introductionmentioning
confidence: 99%